2016
DOI: 10.1002/ecy.1481
|View full text |Cite
|
Sign up to set email alerts
|

Solidago gigantea plants from nonnative ranges compensate more in response to damage than plants from the native range

Abstract: Resistance and tolerance are two ways that plants cope with herbivory. Tolerance, the ability of a plant to regrow or reproduce after being consumed, has been studied less than resistance, but this trait varies widely among species and has considerable potential to affect the ecology of plant species. One particular aspect of tolerance, compensatory responses, can evolve rapidly in plant species; providing insight into interactions between consumers and plants. However, compensation by invasive species has rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 72 publications
0
5
1
Order By: Relevance
“…Finally, defensive strategies in P. australis are further complicated geographically because of strong latitudinal variation in tolerance (this study) and resistance (Bhattarai et al ). Scarcely any other native‐invasive plant systems exist where this level of large‐scale variation in tolerance and resistance is available (but see Liao et al ). Below, we focus on the causes and consequences of variation in P. australis tolerance and conclude with a broader examination of the ramifications of geographic variation in defenses for invasion success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, defensive strategies in P. australis are further complicated geographically because of strong latitudinal variation in tolerance (this study) and resistance (Bhattarai et al ). Scarcely any other native‐invasive plant systems exist where this level of large‐scale variation in tolerance and resistance is available (but see Liao et al ). Below, we focus on the causes and consequences of variation in P. australis tolerance and conclude with a broader examination of the ramifications of geographic variation in defenses for invasion success.…”
Section: Discussionmentioning
confidence: 99%
“…Such shifts in defense allocation would likely facilitate invasion success. Although populations sourced from the invaded range tend to be more tolerant than populations sourced from the native range (Abhilasha and Joshi , Wang et al , Liao et al , Zhang et al ; but see Bossdorf et al , de Jong and Lin ), understanding how tolerance to herbivory mediates invasion success requires a comparison between co‐occurring native and invasive species that share herbivore communities. Many fewer studies have compared tolerance between co‐occurring congeneric or confamilial pairs of native and invasive species, with findings of greater tolerance in invasive species (Ashton and Lerdau , Liu et al ), native species (Zas et al ), or no differences between them (Engelkes et al , Lurie et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive plants have been proven to be capable of rapid evolution in response to stresses, which profoundly contribute to their strong expansion potential (Kollmann & Bañuelos, 2004;Liao, Gurgel, Pal, Hooper, & Callaway, 2016;Poll, Naylor, Alexander, Edwards, & Dietz, 2009). However, how the rapid evolution of tolerance to one stressor may further affect the expansion potential of invasive plants through affecting the responses to other stressful environments has not received much attention.…”
Section: Discussionmentioning
confidence: 99%
“…This could promote compensatory responses from Solidago (Ramula et al 2019). Compensatory responses to damage might enable Solidago to better withstand frequent disturbance as Liao et al (2016) observed, but they did not test the effect of soil biota on this response. Other studies indicate that soil biota may increase compensatory responses in general (He et al 2014; Allsup & Paige 2016).…”
Section: Discussionmentioning
confidence: 99%